ABORDAGENS CONTEMPORÂNEAS NO MANEJO DA ECLAMPSIA: ESTRATÉGIAS PARA MELHORAR RESULTADOS MATERNOS E FETAIS - Silva, Silvano Alves da; Lopes , Thayanne Mayara de Oliveira; Moura , Emilly Gomes de França (Periódicos Brasil. Pesquisa Científica, 2024)
Introduction: Eclampsia represents one of the most severe and challenging obstetric complications, characterized by the development of seizures in women with preeclampsia, a condition marked by high blood pressure and proteinuria during pregnancy. Methodology: The research question was carefully formulated to capture the main advances and practices in the management of eclampsia. The central question defined was: "What are the effective contemporary strategies in managing eclampsia that contribute to the improvement of maternal and fetal outcomes?" Results: Technological advancements have played an increasing role in the management of eclampsia. Advanced imaging technologies, such as Doppler ultrasound, have been used to assess fetal health and placental perfusion, providing valuable information that can guide clinical decision-making. Conclusion: Collaboration among researchers, healthcare professionals, and patients is crucial to promote the advancement of knowledge and the implementation of evidence-based practices in the management of eclampsia, thus ensuring better outcomes for women and their children.